Fatty acids modulate cytokine and chemokine secretion of stimulated human whole blood cultures in diabetes. (18th April 2013) - Simon, M. C.; Bilan, S.; Nowotny, B.; Dickhaus, T.; Burkart, V.; Schloot, N. C.
Summary Fatty acids, uric acid and glucose are thought to contribute to subclinical inflammation associated with diabetes mellitus. We tested whether co‐incubation of free fatty acids and uric acid or glucose influences the secretion of immune mediators from stimulated human whole blood in vitro. Fresh whole blood samples from 20 healthy subjects, 20 patients with type 1 diabetes and 23 patients with type 2 diabetes were incubated for 24 h with palmitic acid (PAL), linolenic acid (LIN) or eicosapentaenoic acid (EPA) alone or together with elevated concentrations of uric acid or glucose. Concentrations of proinflammatory cytokines interleukin (IL)‐1β, IL‐2, IL‐12(p70), IL‐18, IFN‐γ, of regulatory cytokines IL‐4, IL‐10, IL‐17 and chemokine CCL2 (MCP‐1) were measured by multiplex‐bead technology from supernatants. Co‐incubation of fatty acids with uric acid resulted in a significant reduction of IL‐10, IL‐12(p70), IFN‐γ and CCL2 (MCP‐1) concentrations in supernatants compared to incubation with uric acid alone (P < 0·0001). In contrast, IL‐18 was up‐regulated upon co‐stimulation with fatty acids and uric acid. Similarly, co‐incubation of fatty acids with glucose diminished secretion of IL‐10, IFN‐γ and CCL2 (monocyte chemotactic protein‐1), while IL‐8 was up‐regulated (P < 0·001). Samples from healthy and diabetic subjects did not differ after adjustment for age, sex, body mass index and diabetes type. All three fatty acids similarly influenced whole blood cytokine release in vitro and modulated uric acid or glucose‐stimulated cytokine secretion. Although the ω‐3‐fatty acid EPA showed slightly stronger effects, further studies are required to elaborate the differential effects of PAL, LIN and EPA on disease risk observed previously in epidemiological studies.